Contingent valuation of built heritage properties in a transition country: a case of Lithuania - Gražulevičiūtė-Vileniškė, Indrė; Janilionis, Vytautas; Guščinskienė, Jūratė; Ažukaitė, Ligita (International Journal of Strategic Property Management, 2012)
The built heritage began to be seen not only as a real estate property and an object of cultural value but also as a multifaceted and multidimensional cultural good in the second half of the 20th century. It has increasingly attracted the interests of economists, who attempted to measure not only its economic impact, but also the total economic value. The spectrum of the categories of the economic value of the built heritage and the valuation methods applied has expanded in the course of time. Currently it encompasses market and nonmarket economic values and numerous valuation techniques based on the stated and revealed data, including the Contingent Valuation method (CVm). The number of contingent valuation (CV) studies aimed at valuing the non-market benefits of the built heritage in developed and developing countries is growing. However, the post-communist transition countries are quite an exception. The applications of the CVm in the developing countries have demonstrated that the sociocultural context must be taken into account and the special measures must be applied in order to get the reliable results. This sensitivity of the CVm to the sociocultural context encourages analyzing the peculiarities of its application in the post-communist transition countries. The main aim of the article is to determine the peculiarities of the social environment of the post-communist transition countries and their possible influence on the CV results. The findings of the research can be useful not only to the fields of CV survey design and benefit transfer, but also to the broad and rapidly developing field of the post-communist studies, for the better understanding the hidden values and potential of the built heritage properties, and the sustainable management of the built environment. First Publish Online: 11 Jan 2012